¿El habla nativo en un contexto bilingüe Colombiano? (2019)
This article describes how English is seen as the main focus of the bilingual policies in Colombia. In this reflective paper the author’s critical review of different texts is presented to draw attention to bilingualism in the current policies. The importance of the English language is questioned and different views on the Native Speaker and Non-Native Speaker dichotomy are taken into account to describe how a qualified English teacher may be seen in a context where the policies seem not to work well. In the case of Colombia, ambitious programs for English teaching usually favor the status and knowledge of the native speaker over the Colombian teachers who cannot be categorized into what a native model features (Guerrero, 2008). In order to gain understanding different authors’ views were analyzed in regards of the idea of bilingualism and its effects on the Colombian current teaching-learning practices. Even more, the way in which the native speaker myth has shaped the ideal model of language teacher in a context where opportunities to practice English are limited.